1997
DOI: 10.1046/j.1365-2141.1997.552705.x
|View full text |Cite
|
Sign up to set email alerts
|

Interferon increases serum thrombopoietin in patients with chronic hepatitis C

Abstract: Summary.We measured serum thrombopoietin (TPO) in chronic hepatitis C treated with interferon (IFN). The platelet count before the therapy was 161 . 9 × 10 9 Ϯ 64 . 1 × 10 9 /l, which decreased to 116 . 3 × 10 9 Ϯ 48 . 4 × 10 9 /l 1 week after IFN therapy (P < 0 . 01). On the other hand, serum TPO increased from 1 . 96 Ϯ 0 . 60 fmol/ml to 2 . 68 Ϯ 0 . 69 fmol/ml (P < 0 . 02). Contrary to a recent report that serum TPO was not altered in liver cirrhosis, these data indicate that serum TPO was increased in chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 9 publications
(18 reference statements)
0
12
0
1
Order By: Relevance
“…These results confirm the hypothesis of Kuter et al [15] that TPO mediates the feedback loop between circulating platelets and bone marrow megakaryocytes, and that serum levels of TPO are directly determined by the ability of platelets to remove TPO from the circulation. Indeed, serum TPO was inversely correlated with platelet count in patients following chemotherapy [28] and in patients treated with interferon [29]. Thus TPO may increase in response to a reduction in platelet numbers in humans.…”
Section: Discussionmentioning
confidence: 98%
“…These results confirm the hypothesis of Kuter et al [15] that TPO mediates the feedback loop between circulating platelets and bone marrow megakaryocytes, and that serum levels of TPO are directly determined by the ability of platelets to remove TPO from the circulation. Indeed, serum TPO was inversely correlated with platelet count in patients following chemotherapy [28] and in patients treated with interferon [29]. Thus TPO may increase in response to a reduction in platelet numbers in humans.…”
Section: Discussionmentioning
confidence: 98%
“…There have been no reports regarding the relationship between platelet counts and the change of spleen size after IFN therapy. Bizollon et al [22] reported that biochemical and virological responder to combination therapy of ribavirin and IFN associated with marked histological improvement and Shiota et al [23] reported that serum TPO levels increased following SVR to IFN therapy in patients with chronic hepatitis C. Itoh et al [24] showed a significant decrease in fibrosis stage paralleled by an increase in platelet count and serum TPO levels in patients with SVR to IFN therapy after 4 years of follow-up. We also recently reported that the increase of platelet counts and serum albumin and decrease of ZTT associated with improvement of fibrosis in CH-C patients with SVR to IFN therapy [18].…”
Section: Discussionmentioning
confidence: 96%
“…TPO concentrations were found [12,13,16,31,35] (Table 2). Thrombocytopenic patients with severe hepatic diseases, however, showed less pronounced or no increase in the TPO level which might be due to an impaired TPO synthesis in the hepatocytes [15,16,21,38].…”
Section: Controlsmentioning
confidence: 98%
“…In patients with chronic hepatitis C but without liver cirrhosis Shiota et al [31] observed during an interferon therapy elevated serum TPO concentrations as compared to normal individuals while the blood platelet counts were in normal range. Intramuscular or intravenous IFN administration caused during the first week of the therapy a significant decrease in platelet count and a significant increase in the TPO concentration of the serum, the relationship between both parameters were comparable to those of patients without liver disease.…”
Section: Controlsmentioning
confidence: 98%
See 1 more Smart Citation